Oscillatory and evoked neural responses underlying gating in the primary somatosensory cortices: Evidence from optically-pumped magnetometry - Yasra Arif; Elizabeth Heinrichs-Graham; Alexa M. Wildy; Thomas W. Ward; Augusto Diedrich; Christine M. Embury; Maggie P. Rempe; Ryan J. Glesinger; Zhiying Shen; Kellen M. McDonald; Peihan J. Huang; Seth Bashford; et al. (NeuroImage, 2025)
Sensory gating (SG) is a protective mechanism that prevents sensory overload by attenuating neural responses to repeated stimuli while allowing allocation of neural resources to salient inputs. While studies using conventional, cryogenic magnetoencephalography (MEG) have provided a foundational understanding of the neurophysiological spectro-temporal profile of sensory gating in somatosensory cortices, its utility in diverse populations is constrained by technical limitations, including movement restriction and a one-size-fits-all helmet design. Recent developments in optically pumped magnetometry (OPM) aim to overcome these constraints by providing greater tolerance to movement and customizable helmet sizes. A small number of studies have documented the reliability of OPM in mapping somatosensory responses to median nerve stimulation using OPM; however, none have examined SG. In this study, we utilized a whole-head 128-channel OPM system and a paired-pulse median nerve stimulation paradigm to examine somato-SG and map the precise spectro-temporal cortical dynamics in a group of 31 healthy adults. Neural responses per stimulation were imaged in both the time-frequency and time domains, and voxel time series data were extracted to quantify the dynamics of somato-SG. Robust gating effects were observed in the peak and average neural responses within the primary somatosensory cortices, in both the oscillatory and time domains. These findings underscore OPM’s ability to precisely resolve the spatiotemporal neural dynamics of somato-SG and stress the utility of OPM in examining somatosensory processes across developmental trajectories extending down to infants, as well as in clinical populations.